2016
DOI: 10.1007/s00421-016-3412-0
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the revised Ekblom Bak cycle ergometer test in adults

Abstract: PurposeTo further develop the Ekblom Bak-test prediction equation for estimation of VO2max from submaximal cycle ergometry.MethodsThe model group (117 men and 100 women, aged 48.3 ± 15.7 and 46.1 ± 16.8 years, VO2max 46.6 ± 11.1 and 40.4 ± 9.6 mL kg−1 min−1, respectively) and the cross-validation group (60 men and 55 women, aged 40.6 ± 17.1 and 41.6 ± 16.7 years, VO2max 49.0 ± 12.1 and 43.2 ± 8.9 mL min−1 kg−1, respectively) performed 4 min of cycling on a standard work rate (30 W) directly followed by 4 min o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 34 publications
6
124
1
Order By: Relevance
“…The EB test was a valid and reliable test in our study cohort, which indicates that VO 2 max can be accurately estimated in adolescence with this submaximal cycle ergometer test. The present study found that the VO 2 max of prepubertal and pubertal boys and girls aged 10–15 years was estimated within ±0.68 L/min, compared to ±0.65 L/min for men and ±0.53 L/min for women in a mixed adult population in another study . The validity in adolescents seemed to depend on maturity and sex, and the boys in Tanner stages I and II were the most overestimated.…”
Section: Discussioncontrasting
confidence: 41%
“…The EB test was a valid and reliable test in our study cohort, which indicates that VO 2 max can be accurately estimated in adolescence with this submaximal cycle ergometer test. The present study found that the VO 2 max of prepubertal and pubertal boys and girls aged 10–15 years was estimated within ±0.68 L/min, compared to ±0.65 L/min for men and ±0.53 L/min for women in a mixed adult population in another study . The validity in adolescents seemed to depend on maturity and sex, and the boys in Tanner stages I and II were the most overestimated.…”
Section: Discussioncontrasting
confidence: 41%
“…However, measuring actual VO 2 max during maximal performance would not have been feasible in this large non‐athletic population, together with HPA test leaders not experts in work physiology nor with access to laboratory equipment. In addition, assessment of VO 2 max by the Astrand protocol is reported to yield a valid and reliable estimation of actual VO 2 max . Participants on medication that could affect heart rate response during the submaximal test were not excluded in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, VO 2 max was estimated from the standardized Astrand submaximal cycle ergometer test . Criterion validity has been tested for the Astrand test, showing no systematic bias and limited variation in mean difference between estimated and directly measured VO 2 max, mean difference 0.01 L O 2 /min (95% CI −0.10 to 0.11) . All participants were requested to refrain from vigorous activity the day before the test, consuming a heavy meal 3 hours and smoking/snuff use 1 hour before the test, and avoiding stress.…”
Section: Methodsmentioning
confidence: 99%
“…The test was performed on a mechanically braked cycle ergometer (Corival model, Lode Holding Company BV, the Netherlands), and heart rate was measured with a Polar (Polar Electro, RS400 and RS800 model, Kempele, Finland). The maximal volume of oxygen consumption (VO 2 max) was estimated by applying the work rate and mean heart rate of the 5th and 6th minute to the Åstrand normogram, with correction for weight and age …”
Section: Methodsmentioning
confidence: 99%
“…The maximal volume of oxygen consumption (VO 2 max) was estimated by applying the work rate and mean heart rate of the 5th and 6th minute to the Åstrand normogram, with correction for weight and age. 20,21 Physical activity Habitual physical activity was assessed at baseline by the Short Questionnaire to Assess Health enhancing physical activity questionnaire, which is considered a valid and reliable method in older adults. 22 This self-administered questionnaire estimates habitual level of physical activity during a normal week over the past month, with questions about the type, duration, and frequency of activities.…”
Section: åStrand-rhyming Testmentioning
confidence: 99%